“It Always Depends on the Context”: Poker Players' Perceptions of Substance Use at and Beyond the Table - Morvannou, Adèle; Monson, Eva; Saint-Jacques, Marianne; Wagner, Vincent; Aubut, Valérie; Brunelle, Natacha; Dufour, Magali (Critical Gambling Studies, 2023)
While it is well recognized that gambling behaviours are shaped by the contexts in which they occur, less research has investigated the relationship between poker and substance use (i.e., alcohol and other drugs). The current study explores poker players’ perceptions of the relationship between substance use and gambling. This qualitative descriptive study is a secondary data analysis of 25 interviews with poker players conducted as part of a broader prospective cohort project. From the thematic analysis, players described how specific contextual factors, such as social setting and location (e.g., bars, casinos) influenced their substance use. Poker players reported a relationship between substance use and gambling practices. However, players differed greatly in their decisions about whether, and how much, to use alcohol and other drugs, with individuals’ choices depending heavily on contexts (e.g., more inclined to partake when alcohol was available) and motivations (e.g., remaining sober to remain sharp and not impair their intellectual capacity). For those players who considered poker earnings to be their main source of income, increased use of alcohol, tobacco and cannabis were reported as a way of dealing with stress, anxiety and a lack of motivation related to their play.